The effect of royal jelly and silver nanoparticles on liver and kidney inflammation - Hossein Pourmobini; Mohammad Kazemi-arababadi; Mohammad Reza Salahshoor; Shiva Roshankhah; Mohammad Mohsen Taghavi; Zahra Taghipour; Ahmad Shabanizadeh (Mashhad University of Medical Sciences, 2021)
Objective: Royal jelly (RJ) is a honey bee product for which, anti-inflammatory properties were shown in vitro. Nanoparticles, including nano-silver (NS), are plausible inflammation inducers that act by activation of immune cells and consequent production of pro-inflammatory cytokines. This project aimed to explore immunomodulatory effects of royal jelly and nano-silver on the kidney and liver. Materials and Methods: In this project, 40 male rats were grouped as follows: 10 rats as controls, 10 rats treated with RJ; 10 rats treated with both NS and RJ and 10 rats treated with NS. Liver and kidney interleukin (IL)-1β, -2, -6, and -33 levels were determined using commercial ELISA kits. Results: RJ reduced kidney IL-6 levels in comparison to control and NS--RJ groups. RJ and NS reduced kidney and liver IL-1β levels. Kidney IL-33 levels were decreased in the RJ and nano-silver groups in comparison to the NS--RJ group. Conclusion: Based on this study, it may be concluded that RJ together with NS can play anti-inflammatory roles and may affect the function of immune cells.